Development of inactivated-local isolate vaccine for infectious bronchitis - ., Darminto (Indonesian Journal of Animal and Veterinary Sciences, 1999)
Infectious bronchitis (IB) is an acute highly contagious viral respiratory disease of poultry caused by coronavirus. The disease causes high mortality in young chicks, reduce body weight gain in broilers and remarkable drop in egg production. IB can only be controlled by vaccination, but due to the antigenic variation among serotypes of IB viruses, the effective IB vaccine should be prepared from local isolates. The aim of this research is to develop inactivated IB vaccine derived from local IB isolates. Local isolates of IB viruses designated as I-37, I-269 and PTS-III were propagated respectively in specific pathogen free (SPF) chicken eggs, the viruses then were inactivated by formaline at final concentration of 1:1,000. Subsequently, the inactivated viruses were mixed and emulsified in oil emulsion adjuvant with sorbitant mono-oleic as an emulsifier. The vaccine then was tested for its safety, potency and efficacy in broiler chickens. Birds inoculated twice with a two-week interval by inactivated vaccine did not show any adverse reaction, either systemic or local reaction. The inoculated birds developed antibody responses with high titre, while antibody of the control birds remain negative. In addition, efficacy test which was conducted in broilers demonstrated that birds vaccinated by live-commercial vaccine and boosted three weeks later by Balitvet inactivated vaccine showed high level of antibody production which provided high level of protection against challenged virus (76% against I-37, 92% against I-269 and 68% against PTS-III challenge viruses). From this study, it can be concluded that inactivated local IB vaccine is considered to be safe, potent and efficacious. The vaccine stimulates high titre of antibody responses, which provide high level of protection against challenged viruses. Â  Key words: Infectious bronchitis, virus, broiler chicken, antibody, inactivated vaccine